EKSISTENSI TRANSPORTASI ONLINE ERA COVID-19 DITINJAU DARI TRUST DAN SATISFACTION PADA CONTINUANCE INTENTION - Rony Arpinto Ady; Muhammad Afif Setyawan (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to analyze the existence of online transportation services during the Covid 19 pandemic era in terms of the perception of the level of trust and customer satisfaction in influencing continuance intention. The research sample used was 100 respondents using the probability sampling method, which is a random sampling approach to customers or users of online transportation services who are domiciled in the city of Solo Raya. The data analysis method uses multiple linear regression analysis with the help of the SPSS version 25 application. The results show that the level of trust and customer satisfaction both jointly and individually has a significant positive effect on continuance intention of online transportation services in the city of Solo Raya. The conclusion of the study provides important information regarding the existence of online transportation services in the Covid 19 pandemic era in terms of customer trust and satisfaction with continuance intentions in helping various public activities such as delivery, purchasing food/gofood, package delivery, online shopping and so on.